High performance multilayer transformer for RF applications - Nagesh Deevi, Dr; N. Bheema Rao, Dr (International Journal of Engineering and Technology, 2018)
In this paper, multilayer on-chip transformer is proposed to enhance the operation of device in terms of primary quality factor, primary inductance, coupling coefficient and self-resonant frequency. Multilayer transformer is designed by considering the multilevel fabrication concept in RF-VLSI. The demand for miniature on-chip passive components is increased due to the advancement in RF-VLSI design process. The proposed multilayer on-chip transformer is simulated using High Frequency Structural Simulator and the results are compared with conventional planar transformer. The proposed multilayer transformer shows 40% improvement in terms of primary quality factor, 15% improvement in terms of primary inductance and 20% improvement in terms of coupling coefficient when compared to conventional planar transformer. Proposed transformer performance is validated by scaling up the dimensions of transformer from Âµm scale to mm scale and fabricating the transformer on FR4 substrate using PCB fabrication techniques. Measurements of fabricated transformer are carried out using vector network analyser 8719A. Simulated results and experimental results are in good agreement in terms of quality factor, inductance and coupling coefficient. The proposed multilayer transformer is designed using 0.18 Âµm RF-VLSI technology and has an on-chip area of 100-Âµm Ã— 100 Âµm making it compatible for RF integrated circuit (RFIC).Â Â Â